Formulasi Sediaan Krim Ekstrak Etanol Kulit Buah Semangka Merah Sebagai Krim Antijerawat - Tri Puspita Yuliana; Hasratul Kusuma; Puspawan Hariadi; Baiq Maylinda Gemantari (Journal Syifa Sciences and Clinical Research, 2023)
Acne is a problem caused by Propionibacterium acnes bacteria. Red watermelon rind contains lycopene compounds, antioxidants, has tannin and flavonoid compounds and is very good for skin care, free from acne, functions as an antibacterial. The purpose of this study was to formulate ethanol extract of red watermelon rind into anti-acne cream preparation and determine the inhibition zone and determine the red watermelon rind cream has the best antibacterial activity against Propionibacterium acnes bacteria. The method used in this study was experimental, extract concentration of 15%, 20%, 25%. The antibacterial activity test was conducted using the pitting method and evaluated the physical properties of the cream preparation including organoleptic examination, pH test, homogeneity test, adhesion test, spreadability test. The results showed that the evaluation of the physical properties of the cream preparation had characteristics in accordance with the evaluation of the preparation carried out at each concentration, including organoleptic examination, pH test, homogeneity test, adhesion test, spreadability test. The results of the antibacterial activity test of ethanol extract of red watermelon rind F1, F2, F3 are: 6.76 mm, 8.33 mm, 8.73 mm. The results of the antibacterial activity test of the cream preparation of ethanol extract of red watermelon rind F1, F2, F3 are: 4.47 mm, 6.04 mm, 8.17 mm. It can be concluded that the cream preparation of ethanol extract of red watermelon rind meets the characteristics of cream preparation stability, meets the criteria of good physical properties at concentrations of 15%, 20%, 25%, has weak to moderate category antibacterial activity against Propionibacterium acnes bacteria.